Life Cycle Study of a Diabatic Rossby Wave as a Precursor to Rapid Cyclogenesis in the North Atlantic-Dynamics and Forecast Performance - Boettcher, Maxi; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (American Meteorological Society, 2011)
ISSN:1520-0493 ISSN:0027-0644